Investor Risk Aversion and Financial Fragility in Emerging Economies - Riccardo Rovelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2000)
Bank intermediated short-term capital inflows play a crucial role in the financial structure of many emerging economies. Yet since these funds are subject to the risk of early withdrawal, an excessive reliance on this financing is often associated with a financial or currency crisis. We model a situation where withdrawals are motivated by a change in either the domestic or foreign fundamentals. We show that, for a given change in fundamentals, a sudden reversal in the capital flows, and hence a financial crisis, is more likely the more risk averse are the foreign investors. We also show that a policy to tax early withdrawals may discourage the inflows more likely to cause fundamental runs, as it prevents the relatively more risk averse investors from investing. However, the policy must be fine-tuned to avoid discouraging all capital inflows.
Keywords: 330